2022
DOI: 10.1002/anie.202212893
|View full text |Cite
|
Sign up to set email alerts
|

Steric, Electronic and Conformational Synergistic Effects in the Gold(I)‐catalyzed αC−H Bond Functionalization of Tertiary Amines**

Abstract: Direct CÀ H bond functionalization is a useful strategy for the straightforward formation of CÀ C and CÀ Heteroatom bonds. In the present work, a unique approach for the challenging electrophilic Au-catalyzed α-CÀ H bond functionalization of tertiary amines is presented. Electronic, steric and conformational synergistic effects exerted by the use of a malonate unit in the substrate were key to the success of this transformation. This new reactivity was applied to the synthesis of tetrahydro-γ-carboline product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(5 citation statements)
references
References 77 publications
1
4
0
Order By: Relevance
“…With the support of the above experimental results and previous achievements on the generation of α-imino metal carbenes from cyclization of azide–ynamides, , a possible mechanism for the construction of azepino­[2,3- b :4,5- b ′]­diindoles is presented in Scheme . Taking substrate 1a for example, phenyl azide as a nucleophile could initially attack the copper-activated triple bond in 1A to form vinylcopper species 1B , which could smoothly generate α-imino copper carbene intermediate 1C by the release of N 2 .…”
supporting
confidence: 68%
See 1 more Smart Citation
“…With the support of the above experimental results and previous achievements on the generation of α-imino metal carbenes from cyclization of azide–ynamides, , a possible mechanism for the construction of azepino­[2,3- b :4,5- b ′]­diindoles is presented in Scheme . Taking substrate 1a for example, phenyl azide as a nucleophile could initially attack the copper-activated triple bond in 1A to form vinylcopper species 1B , which could smoothly generate α-imino copper carbene intermediate 1C by the release of N 2 .…”
supporting
confidence: 68%
“…The first example of the generation of α-imino gold carbenes via gold-catalyzed azide–alkyne cyclization was developed in 2005 by Toste and co-workers . Under the continuous and in-depth exploration by Zhang, Gagosz, Ohno, Ye, and others over the past decades, this strategy of gold-catalyzed tandem cyclization has become a versatile platform for the synthesis of diverse useful N-heterocycles. Very recently, Gagosz and Ohno demonstrated a very similar methods for synthesizing indole derivatives through gold-catalyzed C­(sp 3 )–H functionalization originating from azide–alkynes.…”
mentioning
confidence: 99%
“…The investigation of the ethyl and isopropyl substrates demonstrated that two isomers can be formed via C ‐cyclization or N ‐cyclization. The selectivity can be controlled by tuning the electron density of the azido‐substituted aryl moiety and the stability of the benzylic carbocation, in combination with adjusting the counter‐anion effect [75] …”
Section: Methodsmentioning
confidence: 99%
“…In our previous work, we reported that hydride migration on α-imino gold carbenes is practical for generating polycyclic indoles 11 (Scheme 3). [30][31][32] Based on extensive research by Gagosz [33][34][35] and Davies, [36] introducing the oxygen functional group facilitates hydride transfer to electrophilic alkynyl gold complexes. Accordingly, we attempted to enhance the hydride transfer step on gold carbenes, via introducing an alkoxy group at the benzylic position, by stabilizing the benzylic cation species H (Scheme 3).…”
Section: Introductionmentioning
confidence: 99%